Public Service Transformation: Optimizing Information Technology Through The Creation of Digital Websites and Applications - Kholilullah; Firdausi; Badrianto (TAAWUN, 2025)
The program aims to build digital awareness and skills in the community by creating an integrated village website and application to address these issues; using a Participatory Action Research (PAR) approach, the program encourages the involvement of village officials and residents in the digital transformation process in the Campor Village. After conducting an analysis, it was found that slow public services are caused by reliance on inefficient manual systems and limited digital access for SMEs. With support from the village government and community participation, the program gradually accelerates administrative processes, increases transparency, and expands market reach for local SME products. Success is reflected in residents' increased access to digital services and optimizing digital platforms for marketing SME products, such as handicrafts and culinary goods. Implementing this technology is expected to be sustainable, providing innovative solutions that strengthen public services and the village economy in the future